Understanding Housing Transitions of Career Women in Indonesia Through Life Course Perspective: Employment as Strategy to Afford Housing - Desti Ayu Setia Hidayati; Joko Adianto; Rossa Turpuk Gabe (International Journal of Built Environment and Scientific Research, 2024)
This qualitative study aims to discover the pivotal factors in housing transitions of Indonesian career women through their life-course events. In Indonesian patriarchal society, women have been struggling to participate in the decision-making process of home making despite their dominant role in everyday domestic activities and thorough understanding of their familial needs. A semi structured interview with seven career women was delivered to examine their housing transitions and the prominent factors of their current housing choice. Through thematic content analysis, this study concludes that the types of employment is the prominent factor of their financial empowerment through their housing transitions, especially for those who are public servants and private employees. Thus, encouraging equal job opportunities for women in their young adult phase would increase household’s affordability to obtain homeownership.